New Dynamics in Latin America - Brunner, Jose Joaquin (International Higher Education, 2013)
The dramatic massification of Latin America's higher education is leading to a social revolution with new demands on government for greater and more effective regulation. However the sector's market development, based on private as much as public institutions and funding, cannot be easily organized. Facing increasing political demands, governments and stakeholders will have to ensure-through innovative instruments and policies-greater quality, employability while adapting funding and curricula to massification, in order to meet the aspirations of Latin America's present and future youth.